Afforestation and abandonment of semi‐natural grasslands lead to biodiversity loss and a decline in ecosystem services and functions - Prangel, Elisabeth; Kasari‐Toussaint, Liis; Neuenkamp, Lena; Noreika, Norbertas; Karise, Reet; Marja, Riho; Ingerpuu, Nele; Kupper, Tiiu; Keerberg, Liis; Oja, Ede; Meriste, Mart; Tiitsaar, Anu; et al. (The Journal of applied ecology, 2023)
During the past century, semi‐natural grasslands, once widespread throughout Europe, have largely been converted into intensively managed agricultural areas, abandoned or afforested. These large‐scale land‐use changes have already resulted in considerable biodiversity loss but can also lead to decline in ecosystem service provision and ecosystem multifunctionality. We assessed the impact of afforestation and abandonment of semi‐natural grasslands on the supply of ecosystem services in Western Estonia. We compared a wide array of services provided by open grasslands, abandoned grasslands and afforested grasslands. Additionally, we analysed the impact of land‐use change and species richness on ecosystem multifunctionality. Significant declines in the supply of pollination services, natural pest regulation, forage production, soil quality, wild food and cultural appreciation of landscape were detected as a result of overgrowing or afforestation. There was significant positive relationship between species richness and ecosystem multifunctionality, that is, more biodiverse grasslands were able to support more services at higher capacity. Results show that both grassland degradation due to abandonment, as well as grassland afforestation, have significant negative impacts on biodiversity, on the supply of multiple important ecosystem services and on the ecosystem multifunctionality. Synthesis and applications. Temperate semi‐natural grasslands have high biodiversity and capacity to deliver multiple important ecosystem services simultaneously. Conservation and restoration of grassland habitats must be considered as an important part of sustainable landscape planning. Temperate semi‐natural grasslands have high biodiversity and capacity to deliver multiple important ecosystem services simultaneously. Conservation and restoration of grassland habitats must be considered as an important part of sustainable landscape planning.